1986
DOI: 10.1037/0096-3445.115.3.267
|View full text |Cite
|
Sign up to set email alerts
|

External and internal memory aids: When and how often do we use them?

Abstract: Low Publication Prices for APA Members and Affiliates Keeping You Up-to-Date All APA members (Fellows, Members, and Associates) receive-as part of their annual dues-subscriptions to the American Psychologist, the APA Monitor, and Psychology Today. High School Teacher and Student Affiliates receive subscriptions to the APA Monitor and Psychology Today, and they can subscribe to the American Psychologist at a significantly reduced rate. In addition, all members and affiliates are eligible for savings of up to 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
106
0
1

Year Published

1990
1990
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(112 citation statements)
references
References 32 publications
5
106
0
1
Order By: Relevance
“…When the mnemonic strategies are separated into those that are external and those that are internal (see column labeled "Type"), it is clear that the participants reported using the external mnemonics much more frequently than internal ones. This confirms similar findings by Intons-Peterson and Fournier (1986) for college students, and by Harris (1980, second study), whose participants were housewives from a study panel with a mean age of 46 years. In fact, the rankings of the frequency of use of these mnemonics as reported by the present participants and Harris's panel of housewives are nearly identical (Spearman correlation = .94 with ranking based on proportion reporting using the mnemonic more than once a week).…”
Section: Forced-choice Questionssupporting
confidence: 78%
“…When the mnemonic strategies are separated into those that are external and those that are internal (see column labeled "Type"), it is clear that the participants reported using the external mnemonics much more frequently than internal ones. This confirms similar findings by Intons-Peterson and Fournier (1986) for college students, and by Harris (1980, second study), whose participants were housewives from a study panel with a mean age of 46 years. In fact, the rankings of the frequency of use of these mnemonics as reported by the present participants and Harris's panel of housewives are nearly identical (Spearman correlation = .94 with ranking based on proportion reporting using the mnemonic more than once a week).…”
Section: Forced-choice Questionssupporting
confidence: 78%
“…Studies have demonstrated that in their everyday lives older adults use memory strategies less often than younger adults (Devolder & Pressley, 1992). When memory strategies are used they are more often external (list, notes, person) rather than internal (association, rehearsal, memory strategies (Intons-Peterson & Fournier, 1986;McDougall, 1995b).…”
Section: Everyday Memorymentioning
confidence: 99%
“…Studies have demonstrated that in their everyday lives older adults use memory strategies less often than younger adults (Devolder & Pressley, 1992). When memory strategies are used they are more often external (list, notes, person) rather than internal (association, rehearsal, memory strategies (Intons-Peterson & Fournier, 1986; McDougall, 1995b).Episodic memory stores information about when events happened and the relationship between those events. Everyday memory relates to how memory operates in ordinary situations and circumstances--norms and habits (Cohen, 1989).…”
mentioning
confidence: 99%
“…Although it produces external feedback and therefore may share some characteristics of external aids, it is not entirely external because the purpose ofrepeated writing is to learn the items by heart while writing, but not to make an external prompt or a reminder note for later use; that is, it is the writing action itself, not the output, that is important. Interestingly, while it does not appear in the list of 19 memory aids put up by Intons-Peterson and Fournier (1986), repeated writing was shown to be one of the most popular memory aids among Japanese subjects (Kusumi, 1992).…”
mentioning
confidence: 99%
“…Some, such as reminder notes, are external, while others, such as mental rehearsing, are internal. In general, external aids are preferred (Harris, 1984), but internal aids are used when one cannot rely on external prompts or when external aids would be undesirable or inconvenient (Intons-Peterson & Fournier, 1986). In the latter conditions, a memory aid that is commonly used by the Japanese is repeated writing, or rehearsal by writing, which involves writing down to-be-remembered items over and over on a piece of paper, on a table top, or even in the air.…”
mentioning
confidence: 99%